Law and order in plants – the origin and functional relevance of phyllotaxis. (October 2022) - Reinhardt, Didier; Gola, Edyta M.
Abstract : The regular arrangement of organs (phyllotaxis) in vegetative shoots and flowers is one of the most stunning features of plants. Spiral patterns characterized by Fibonacci numbers have attracted the particular interest of natural scientists and mathematicians. Numerous reviews have dealt with the molecular genetic mechanisms underlying phyllotaxis, and modeling studies have sought to recreate phyllotaxis according to mathematical, biochemical, or physical laws. However, what is the functional significance of regular plant architecture, and how did it evolve? We discuss the developmental constraints and selective forces that may have favored the selection of phyllotaxis, and we argue that a central driver of regular phyllotaxis may have been limitations in the allocation of founder cells and metabolic resources to the different tissues in the shoot apex. Highlights: The regular arrangement of leaves and floral organs around the stem (phyllotaxis) is ubiquitous in plants. Regular phyllotaxis appears to be more important for basic meristem function than for final plant architecture. Phyllotaxis is intimately linked to meristem organization. In early-diverged plants (e.g., mosses) the division pattern of the apical stem cell defines leaf arrangement. In angiosperms an auxin-related patterning machine controls phyllotaxis. Phyllotaxis is intimately linked to organogenesis; therefore, very few mutants have a separate phenotype in only one of these traits. Based on the few dominating phyllotactic patterns observed in nature, developmental and metabolic constraints are likely to act on morphogenesis and growth at the shoot apex.